A case study on Ar Rahnu facility in Bank Rakyat Malacca / Linda Nasaruddin Sia - Nasaruddin Sia, Linda (Faculty of Business and Management, 2009)
Ar-Rahnu scheme is the main source of funds for those who need loans immediately for a specific period. The majority of the customers of the scheme generally do not have access to other sources of funds or do not have the capacity to obtain loans or financing from financial institutions. The issues that would like to highlight in this study is regard the comparison between Islamic Pawnshop and the Conventional Pawnshop. The data gathered from both primary data and secondary data. The findings are from sources Bank Rakyat which the disbursement and the number of account of Ar Rahnu. It has been identified that there is increasing of disbursement and the number of account. Bank Rakyat has achieved their target for as the gap identification of their operation. Furthermore, the studies also show the modus operandi of Conventional and Islamic pawnshop and the weaknesses of Conventional Pawnshop. Base on the result of this study, some recommendation has been proposed which hopefully can help them to improve their business performance in future.